Protein-restricted diets plus keto/amino acids--a valid therapeutic approach for chronic kidney disease patients - Aparicio, Michel; Bellizzi, Vincenzo; Chauveau, Philippe; Cupisti, Adamasco; Ecder, Tevfik; Fouque, Denis; Garneata, Liliana; Lin, Shanyan; Mitch, William E; Teplan, Vladimír; Zakar, Gábor; Yu, Xueqing (Journal of renal nutrition, 2012)
Chronic kidney disease (CKD) is increasingly common, and there is an increasing awareness that every strategy should be used to avoid complications of CKD. Restriction of dietary protein intake has been a relevant part of the management of CKD for more than 100 years, but even today, the principal goal of protein-restricted regimens is to decrease the accumulation of nitrogen waste products, hydrogen ions, phosphates, and inorganic ions while maintaining an adequate nutritional status to avoid secondary problems such as metabolic acidosis, bone disease, and insulin resistance, as well as proteinuria and deterioration of renal function. This supplement focuses on recent experimental and clinical findings related to an optimized dietary management of predialysis, dialysis, and transplanted patients as an important aspect of patient care. Nutritional treatment strategies are linked toward ameliorating metabolic and endocrine disturbances, improving/maintaining nutritional status, as well as delaying the renal replacement initiation and improving outcomes in CKD patients. A final consensus states that dietary manipulations should be considered as one of the main approaches in the management program of CKD patients and that a reasonable number of patients with moderate or severe CKD benefit from dietary protein/phosphorus restriction.